GEOPHYSICAL AND WELL CORELLATION ANALYSIS OF OGO FIELD: A CASE STUDY IN NIGER DELTA BASIN OF NIGERIA (Nigerian Journal of Technology, 2017)
A suite of geophysical wire line logs were run in hole. The wells data were acquired from bottom to top and not top to bottom. Basically, we have the qualitative and the quantitative evaluation techniques.Qualitative means is usually used for identification of the type of lithology and also for the component of the formation. Quantitative is used to estimate numerically, the value of what is in the formation. The logs used for evaluation were: Spontaneous potential logs and the Gamma ray logs. These were used to determine the lithology of the formation. Resistivity logs were run in hole to also determine the water saturation in the formation. The Formation Density and the compensated Neutron logs were run in hole to differentiate the gaseous zone from the oil zone in the Hydrocarbon Formation Ogo1, Ogo2 and Ogo3 from well correlation depicts that the subsurface stratigraphy is that of sand – shale intercalations.  Two prominent hydrocarbon bearing reservoirs (R1and R2), at Depth 1563m and 1642mm respectively were identified. The reservoirs were found to have average porosity of 0.22, water saturation 0.43 and Hydrocarbon saturation of 0.57. The reservoirs have permeability of 1376m, volume of oil in place for reservoir 1 and 2 is 39900m3  and 9647 m3   respectively. More. Well correlations are recommended for proper drilling and well completions. 4D seismic acquisitions should be encouraged for proper view of the formation. http://dx.doi.org/10.4314/njt.v36i3.10